Pemanfaatan Mesin Penggiling Jagung Untuk Mereduksi Biaya Pakan Pada Usaha Pengelolaan Ternak Ayam - Suparmono; Sibarani, Baringin; Khairina, Isni; Nasution, Harris Pinagaran; Safitri, Habibi Ramdani (Jurnal Ilmiah Madiya (Masyarakat Mandiri Berkarya), 2024)
The high price of chicken feed makes it difficult for farmers to develop their livestock business. This is also experienced by Mr. Pardamiyan Siregar, who has 50 chickens of various ages. Chicken is a type of livestock that relatively eats any kind of food, including grains, green vegetables, and household leftovers. It is easy to feed chickens, including the food scraps mentioned above, but it is not always available, and the amount is minimal. Therefore, this service partner must provide feed through ground corn and fine rice bran purchased at animal food stores. The cost that partners must incur is IDR 47,000 per day or IDR 1,410,000 per month. The partner wishes to reduce the feed cost by grinding the round corn purchased from the store. The desire is based on the price difference between round and ground corn. The price of round corn is only IDR 6,000/kg, while ground corn is IDR 8,000/kg so that the partner can save IDR 2,000/kg in feed costs. If the amount of ground corn given to livestock is 3 kg, then partners can save IDR 8,000 daily. The high cost of feed procurement and the promising profit prospects encourage partners to collaborate with the implementation team to find solutions to the problems faced by partners. According to the implementation team, the most appropriate solution to overcome partner problems is the provision of assistance with corn grinding machines. To achieve maximum success in helping partners, the program implementers arranged the following implementation steps: location surveys and interviews to explore the main problems, analyze the situation and conditions of the partner's business, determine solutions, prepare the implementation of machine manufacturing programs, machine grants, training, and program evaluation. The result of this service program is one unit of corn grinding machine with a capacity of 50 kg/hour. The machine uses a 1.5 hp electric motor drive with a grinder rotation of 180 rpm. The size of the corn grains produced ranges from 1 mm to 2 mm. This grain size allows it to be eaten by chickens (poultry) of all ages.